1994
DOI: 10.1159/000106723
|View full text |Cite
|
Sign up to set email alerts
|

Are Gait Disturbances and White Matter Degeneration Early Indicators of Vascular Dementia?

Abstract: The objective of this study was to correlate clinical and brain imaging findings with walking inabilities in patients with possible vascular dementia. For 24 patients with suspected initial vascular dementia according to DSM-III-R, structured neurological, neuropsychological and neuroimaging (magnetic resonance tomography) examinations were evaluated alongside computerized gait analysis. All patients revealed an increased variability of gait lines of various degrees: mild (11%), moderate (32%) and severe (57%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 7 publications
2
31
0
1
Order By: Relevance
“…Blood cells from 21 patients (12 men and 9 women) with subcortical vascular encephalopathy (SVE) [13,[18][19][20] following the diagnostic criteria for research studies (NINDS-AIREN) [21] were used as a second group of demented patients, to elucidate differences in pathogenesis. Patients underwent a structured medical and neurological examination as well as neuropsychological interviews following a research protocol with particular emphasis on the presence of motor and gait disturbances, urinary incontinence, memory and attention disorders, frontal release signs, and aspontaneous episodes.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood cells from 21 patients (12 men and 9 women) with subcortical vascular encephalopathy (SVE) [13,[18][19][20] following the diagnostic criteria for research studies (NINDS-AIREN) [21] were used as a second group of demented patients, to elucidate differences in pathogenesis. Patients underwent a structured medical and neurological examination as well as neuropsychological interviews following a research protocol with particular emphasis on the presence of motor and gait disturbances, urinary incontinence, memory and attention disorders, frontal release signs, and aspontaneous episodes.…”
Section: Subjectsmentioning
confidence: 99%
“…Therefore, we included in our present study a well-characterized group of patients with subcortical vascular encephalopathy (SVE) [13]. Very interestingly, specific differences in intracellular calcium signalling have been already reported between AD and SVE [14].…”
Section: Introductionmentioning
confidence: 99%
“…14 However, expression and release of adhesion molecules have not been investigated in different cerebrovascular diseases, ie, in patients with intracranial stenoses or in patients with subcortical vascular encephalopathy (SVE), a small-vessel disease characterized clinically by progressive dementia, emotional lability, gait disorders, and incontinence and neuroradiologically by subcortical diffuse periventricular white matter lesion and lacunes. [15][16][17] It is unclear why many patients have large-vessel disease without apparent cerebral microangiopathy, whereas others suffer selectively of cerebral microangiopathy. To obtain further information about differences and similarities regarding possible inflammatory endothelial activation, which is currently thought to play a role in atherogenesis, soluble adhesion molecules that are derived from activated endothelium were analyzed in cerebral macroangiopathy and microangiopathy.…”
mentioning
confidence: 99%
“…Early descriptive studies reported gait difficulties, including wide base of support, short step length, increased step variability and turning "en bloc", in subjects with subcortical white matter lesions. (Thompson and Marsden 1987;Hennerici et al 1994;Baloh et al 1995;Briley et al 1997;Camicioli et al 1999;Ebersbach et al 1999). In addition, casecontrol studies demonstrated that the severity of white matter damage was associated with greater falls risk.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that damage to white matter tracts between the motor areas in the cortex, basal ganglia, thalamus and cerebellum interfere with the motor output to the lower extremities during balance tasks. (Hennerici et al 1994;Tell et al 1998;Guttmann et al 2000;Wolfson 2001;Onen et al 2004) The current preliminary study seeks to augment the information gained from previous work by explicitly testing the hypothesis that the degeneration of frontal-subcortical white matter pathways that are involved in motor function are related to deficits in postural performance that are served by these pathways. Consequently, in this study we used a sensory-cued choice reaction time (CRT) step task as a model for examining whether lesions in the white matter are associated with specific balance impairments (e.g.…”
Section: Introductionmentioning
confidence: 99%